The detective genre in literature and the work of Kemel Tokayev - Zhunussova А.К.; Rakymzhan Р.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The detective genre, reflecting the shadow sides of society, negative human traits through criminal cases, has its own history and influence. It is obvious that in world literature this genre has developed in many ways and is expanding its boundaries. But the detective genre in Kazakh literature remains unexplored to this day, despite the fact that detective works are currently in great demand in our country. Therefore, the article will consider the works of Kemel Tokayev, who made a special contribution to the development of the detective genre of Kazakh literature, and a literary and theoretical analysis of plot events and character systems will be carried out. Differences and similarities, features of works of world literature, types and characters of characters are also studied. In particular, his works "The Conspiracy" ("Kastandyk"), "The Soldier went to war" ("Soldat sogyska ketti") are compared with the works of foreign writer Edgar Allan Poe, Turkish writer Ahmet Umit and various examples-facts are given. The named works consistently state the thematic, artistic features, genre nature of the writers, describe the orientation, actions, psychology, age, the search for the investigator. The authors of the article add their own opinions, taking into account the scientific conclusions presented in the works of critics, scientists on this topic. In addition, a conclusion is formed about the direction of development and about the general features and differences of the detective genre with world literature.